The Effect of Time of Retention Test and Interference on Implicit Motor Memory Consolidation - Parvaneh Shamsipour Dehkordi; Behrouz Abdoli; Mehdi Namazizadeh; Hassan Ashayeri (رشد و یادگیری حرکتی ورزشی, 2018)
The aim of this study was to compare the effect of time courses of interference and retention test on implicit motor memory consolidation. 60 right-handed female students who had cognitive, mental and physical health and novice at performing alternating serial reaction time task (ASRTT) and serial color matching task (SCMT) (mean age=21.95+1.95 years) were randomly divided into three groups of interference with distances of 6, 24 and 72 hours after the practice session. In the acquisition phase, all groups practiced the ASRTT in 25 blocks of 80 trials in one day. Then, they participated in the second interference task (SCMT) 6, 24 and 72 hours after the practice session and participated in the retention test 24 hours later. In the acquisition phase, subjects’ performance improved with an increase in the practice trials and they had better performance in the 5th practice block (P<0.001). In retention test, there was no significant difference between mean reaction time in the 5th practice block and retention test of the first group (interference with the 6 hours distance). There was a significant difference between mean reaction time in the 5th practice block and retention test of the second group (interference with the 24 hours distance) and the third group (interference with 72 hours distance). The third group (interference of 72 hours distance) had the best performance while the first group (interference with the 6 hours distance) had the weakest performance. Therefore, the interference distances of 24 and 72 hours after the acquisition session led to memory consolidation.